The Impact of Trade Agreement and War on Specific Indonesia-China Bilateral Trade - Christieni Maria (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
This research aims to evaluate the impact of trade agreements and trade war on specific Indonesia-China bilateral trade on four export-import commodities during 2014 - 2019. The methodology used are both descriptive analysis and RCA and EPD analysis. The entire analysis section tries to focus on important periods of economic relations between Indonesia and China, namely the implementation of the 2015 ACFTA and trade war. The results of the study indicate that Indonesia's selected export commodities have huge potential to be developed in bilateral trade with China, especially to maximize the benefits of ACFTA. The implementation of ACFTA 2015 has a positive impact on the growth of the four selected commodities as well as on its competitive analysis. The results of RCA analysis show the four commodities remain including highly competitive, even for palm oil tends to be specialized for Indonesia, however there are differences from EPD analysis results where the two Indonesian export commodities (Animal or Vegetable Fats/ HS15 and Mineral Fuels/HS27) before the trade war was in the rising star position, it became a lost opportunity, but for the two imported Indonesian commodities, there was no change in staying in the rising star position.